TRANSFORMASI STRUKTUR EKONOMI KABUPATEN SIAK TAHUN 2001-2010 - Yudha Prawira; Wahyu Hamidi (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2013)
This paper attempts to analyzes spatial structural change of economic andidentification of base sector in Siak District. The data used in this paper are timeseries (secondary data) consists of the Gross Regional Domestic Product (GRDP)Siak District and Gross Regional Domestic Product (GRDP) Riau Province at2000 Constant Market Price by Industrial Origin Excluding Oil 2001-2010. Thedata obtained from Central Bureau of Statistics Riau Province. The analysismethods applied in this study are Shift Share Analysis, Shift Share ModificationEsteban Marquillas, Location Quotient and Base Multiplier. The Results of thestudy analysis known that: Contribution of the primary sector in total GRDP hasdecreased during the period analysis, while the contribution of secondary andtertier sector has increased over the analysis period. Increased the level of GRDPin Siak by 112.70% due to the effects of economic growth in the level of RiauProvince. Effect of economic competitiveness of negative 14.28 %, while theinfluence of the Industrial Mix only by 1.58 %. GDRP growth is the largest frommanufacture sector amounted to Rp 928,774.54 million, national share of thissector amounted to 113.43%, differential shift of negative 33.62% andproportional shift of 20.18 %. From Esteban Marquilass Shift Share analysis onlyagriculture and construction has a competitive advantage and manufacture sectorhas only the specialization advantage. LQ analysis shows that base sector in Siakhas only manufacture sector. Average value of base multiplier effect of Siak are1.9, it means sector basis can give impact to the GRDP formation by 1.9 times ofthe total output.Kata Kunci:Spatial structural change, GRDP, Shift Share, LocationQuotient, Base Sector, Base Multiplier Effect